Perancangan Sistem Informasi Penjualan Dan Stok Berbasis Web Multi-Cabang Pada Mochi Petshop - Nabil Syawaludin Prima; Triana Elizabeth (STMIK Banjarbaru, 2026)
This study focuses on Mochi Petshop, a business for pet equipment managing multiple physical stores in Palembang. At present, cashier recording and inter-store inventory management are not yet computerized, often triggering slow data recapitulation, item quantity discrepancies, and obstacles in monitoring daily performance. This study aims to design a multi-branch, web-based sales and inventory information system using the Laravel framework. This research adopts the Rapid Application Development (RAD) model as its development approach. The workflow of this method encompasses four primary phases: initial specification planning, interface design, program coding process, and full operational transition. The developed system supports the management of sales transactions, stock-in, stock-out, inter-branch stock transfers, product returns, and real-time reporting. The Black Box Testing results indicate that all system features operate according to the specified requirements, proving that the system is capable of enhancing data management effectiveness and operational efficiency at Mochi Petshop.Keywords: Sales information system; Inventory; Multi-branch; Laravel; RAD AbstrakPenelitian ini mengambil studi kasus pada Mochi Petshop, sebuah bisnis perlengkapan hewan yang mengelola sejumlah gerai fisik di Palembang. Saat ini, pencatatan kasir dan manajemen persediaan antartoko belum terkomputerisasi, sehingga sering memicu rekapitulasi data yang lambat, selisih jumlah barang, serta kendala dalam pengawasan kinerja harian. Penelitian ini bertujuan merancang sistem informasi penjualan dan stok berbasis web multi-cabang menggunakan framework Laravel. Penelitian ini mengadopsi model kerja Rapid Application Development (RAD) sebagai pendekatan pengembangannya. Alur metode ini mencakup empat fase utama, yakni: perencanaan spesifikasi awal, perancangan antarmuka, proses pengkodean program, serta transisi operasional penuh. Sistem yang dibangun mendukung pengelolaan transaksi penjualan, stok masuk, stok keluar, perpindahan barang antar cabang, retur barang, dan laporan secara real-time. Hasil pengujian Black Box Testing menunjukkan seluruh fitur sistem berjalan sesuai kebutuhan sehingga sistem mampu meningkatkan efektivitas pengelolaan data dan efisiensi operasional pada Mochi Petshop.